Perancangan Interior Toko Tas Elizabeth di Semarang - Tan Hendarto Lukito; Muhammad Solahuddin; Grace Mulyono (Intra, 2013)
The meaning of Elizabeth Bag Store Interior Design in Semarang is map out Elizabeth bag store interior with design concept be in the form of design ideas, design themes, ideas or themes characteristic and ideas or themes application in bag store's interior. Elizabeth bag store is designed with post modernism style which is contained modern style, colonial style and java etnic. The modern style application in Elizabeth bag store's can be found at simple furniture's shape but elegant and apply materials like glass, stainless stell and gloss finishing. The colonial style application in Elizabeth bag store's can be found at window's design, high platform and chandlier lamp. The java etnic style application in Elizabeth bag store's can be seen at wood texture finishing.